PENERAPAN INKUIRI UNTUK MENINGKATKAN KEMAMPUAN MENYAMPAIKAN PENDAPAT DISKUSI SISWA DI SMAN 2 SELIMBAU - Utami Sri Rahayu; Nanang Heryana; A. R. Muzammil (Universitas Tanjungpura, 2017)
AbstractBased on interviews with teachers of Indonesian subjects in grade X SMA Negeri 2 Selimbau Kapuas Hulu obtained information that of the four skills of learning Indonesian Language and Literature are students are very lacking in the ability to speak. One of the alternative methods that can be developed to overcome the low learning outcomes in Indonesian subjects is to apply the Inquiry learning model because students can find their own way to solve the problem. This study aims to describe the learning activities convey opinions in the discussion by using the model Inkuiri in class X SMA Negeri 2 Selimbau Kapuas Hulu The research method used is descriptive method. This research was conducted in class X Secondary High School State 2 Selimbau Kapuas Hulu Regency. Data collection techniques used in diresct observation, direct communication and measurement. The data collection tools used are observation guides, interview guides and tests. Data analysis used is qualitative data analysis. Learning outcomes in the discussions after using the Inkuiri model contributed significantly to student learning outcomes. In cycle I the classical average value is 65,91 and in cycle II becomes 81,76. Keywords: Inquiry Learning Model, Delivering Opinions in Discussion